Associations of microRNA Gene Polymorphisms With Salt Sensitivity, Longitudinal Blood Pressure Changes, and Hypertension Incidence in the Chinese Population - Xi Zhang; Shi Yao; Yang Wang; Chao Chu; Mingfei Du; Jianjun Mu (The Journal of Clinical Hypertension)
ABSTRACT MicroRNAs (miRNAs) are small endogenous RNA molecules that play an essential role in various disease processes including elevated blood pressure (BP). Although the effects of dietary salt and potassium intake on BP regulation have been established, their co‐interaction with miRNAs are still unclear. The purpose of the current study was to explore the connection between miRNA gene polymorphisms and BP response to salt and potassium intake, and the relationship between miRNA gene polymorphisms and long‐term BP changes and hypertension development. A total of 333 participants underwent a chronic sodium‐potassium dietary intervention trial, which included a 3‐day normal diet, followed by a 7‐day low‐salt diet, then a 7‐day high‐salt diet, and finally a 7‐day high‐salt with potassium‐supplemented diet. This cohort was subsequently followed for up to 14 years. Single‐nucleotide polymorphisms (SNPs) rs115254818 in miR‐26b‐3p, rs11191676 and rs2292807 in miR‐1307‐5p, and rs4143957 in miR‐382‐5p were significantly correlated with systolic BP (SBP) and mean arterial pressure (MAP) responses to high‐salt intake, whereas rs11191676 and rs2292807 in miR‐1307‐5p exhibited significant associations with SBP response to potassium‐supplemented diet. Furthermore, SNPs rs2070960 in miR‐3620‐5p and rs12364149 in miR‐210‐3p demonstrated significant correlations with diastolic BP and MAP alterations at 14 years of follow‐up. Generalized linear mixed model analysis revealed a significant association between rs2070960 in miR‐3620‐5p and hypertension development over a 14‐year period. Our study indicates that miRNA gene polymorphisms are pivotal in the salt and potassium sensitivity of BP, as well as in the longitudinal BP progression and hypertension incidence. Trial Registration: ClinicalTrials.gov identifier: NCT02734472